G406(P) Oral formulation-related barriers to medicines administration in children with chronic conditions: views of parents and young people. (7th April 2014) - Venables, RH; Stirling, HF; Marriott, JF
Abstract : Introduction: Limited studies have explored oral formulation-related barriers to medicines administration in children, in narrow patient groups (e.g. HIV). Owing to the lack of licensed medicines suitable for use in children, often manipulation is required to either deliver a dose or to facilitate medicines administration. The need for more age-appropriate medicines has been well acknowledged [1]. Purpose: This study adopted a pragmatic approach to determine the nature and prevalence of oral formulation-related barriers to medicines administration in children suffering from a wide range of chronic conditions. Problems reported by patients and their parents/carers about oral formulations were identified with the aim of informing future pharmaceutical development, thus improving future children's medicines. Materials and methods: Semi-structured face-to-face interviews were conducted with 278 parents/carers/young people at UHCW. Children (0- <18 y) were receiving prescribed medicines for a chronic condition (duration ≥1 month). Questions explored barriers to medicines administration, medicines refusal and manipulation. Ethical approval was granted. Results: Medicines refusal 19% of all medicines were reported to be refused by childrenTaste was a problem reported for 64% of medicines that were refused. Medicines manipulation 19% of all medicines were reported to be manipulated 79% of manipulations were for the purpose of administering a specific dose (e.g. tablet segmented)26% of manipulations were to facilitate administration (e.g. mixed with foodstuffs). Oral formulation-related barriers to medicines administration: Taste was the most commonly reported (35% of all prescribed medicines) Drugs with highest incidence of taste issues were ranitidine liquid (82%), prednisolone soluble tablets (81%) and trimethoprim liquid (75%) of total usersIssues also reported (in descending order of prevalence) were: texture (8%), volume/quantity (5%), size/swallowing (5%), colour (2%) and smell (2%). Conclusions: In total, 19% of medicines were reported to be refused by children. For administration to children, almost one fifth of medicines were reported to require manipulation. Taste was most the most frequently reported oral formulation-related barrier to medicines administration. Findings indicate that age-appropriate medicines should be developed to provide both suitable dose units and acceptable taste for paediatric patients. Reference: 1. EMEA (2006) Reflection paper: formulations of choice for the paediatric population. London. EMEA/CHMP/PEG/194810/2005. p1–45. [Online] Available at: http://www.ema.europa.eu/docs/en_GB/document_library/Scientific_guideline/2009/09/WC500003782.pdf [Accessed on 17/05/2013].